2019
DOI: 10.3389/fphar.2019.00172
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on PARP14 as a Drug Target

Abstract: Poly-adenosine diphosphate-ribose polymerase (PARP) implements posttranslational mono- or poly-ADP-ribosylation modification of target proteins. Among the known 18 members in the enormous family of PARP enzymes, several investigations about PARP1, PARP2, and PARP5a/5b have been launched in the past few decades; more specifically, PARP14 is gradually emerging as a promising drug target. An intact PARP14 (also named ARTD8 or BAL2) is constructed by macro1, macro2, macro3, WWE, and the catalytic domain. PARP14 ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 72 publications
(107 reference statements)
1
43
0
Order By: Relevance
“…Interestingly, the gene that showed the highest significance was PARP14 ( Figure S1E). This has been previously reported to play a role in chemoresistance (17). Our analysis also highlighted one gene (ZNF292) showing lower expression in the relapseenriched clone and that was significantly correlated to poorer prognosis of tumors displaying low expression.…”
Section: The Expression Profile Of the Relapse-enriched Clone Predictsupporting
confidence: 75%
“…Interestingly, the gene that showed the highest significance was PARP14 ( Figure S1E). This has been previously reported to play a role in chemoresistance (17). Our analysis also highlighted one gene (ZNF292) showing lower expression in the relapseenriched clone and that was significantly correlated to poorer prognosis of tumors displaying low expression.…”
Section: The Expression Profile Of the Relapse-enriched Clone Predictsupporting
confidence: 75%
“…In case of PARP14, physiological ADPribosylation only targeted tyrosine residues, similarly setting it apart from PARP1 and PARP2 which were primarily modified on serine residues. Auto-modification of PARP14 has been described previously (Qin et al, 2019), and the interactome of PARP14 suggests a role in regulating RNA stability (Carter-O'Connell et al, 2018). We detected modification of PARP13 in cells on one cysteine residue, and PARP14 has been demonstrated to MARylate PARP13 in vitro (Carter-O'Connell et al, 2018), although there acidic amino acids were targeted for modification.…”
Section: Discussionmentioning
confidence: 91%
“…PARPs have been targets for drug development, particularly in the cancer field. The most active targets include PARP1, and more recently PARP14 (Berger et al 2018;Qin et al 2019). Studies that used the small molecule inhibitors demonstrated that PARP suppression reduces proinflammatory responses or enhances anti-inflammatory functions of macrophages (Haskó et al 2002;Wang et al 2013;Shrestha et al 2016;Dharwal et al 2019).…”
Section: Parps In Cancer Immunologymentioning
confidence: 99%